The expression of the gene for Azurin from Alcaligenes denitrificans in E. coli : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Biochemistry at Massey University - Bateson, Joseph Anthony (Massey University, 1994)
Azurin is a protein which funtions in electron transport and has been found to bind copper when it is expressed in its native bacterial host. In this thesis the azurin from Alcaligenes denitrificans was used. This protein is 129 amino acids long with a molecular weight of 14. 600 dalions. The azurin coding gene from Alcaligenes denitrificans had previously been cloned into a plasmid which allows an E. coli expression system to be used. Azurin was purified from the E. coli hosts using the same procedures as for purifying copper-azurin from the native hosts but was found to remain apparently impure, according to spectrophotomctric data. Efforts to increase the production of the protein by using different expression systems and by refining the existing expression system failed to increase the apparent yield of copper-azurin. Efforts to refine the purification procedure also failed to increase the amount of copper-azurin that was purified. Various experiments were performed to demonstrate that azurin was expressed and processed correctly in the E. coli host. Protein was expressed in a copper-rich and copper-sparse environment. Copper-azurin was purified from the copper-rich environment, while very little copper-azurin could be extracted from the copper-sparse environment. The results described in this thesis suggest that when azurin from A. denitrificans is expressed in an E. coli host using standard media with no copper added, the predominant form of azurin produced in zinc-azunn. As mutants are going to made of this protein, conditions where the protein would bind only copper were required. The ideal conditions for this are still to be calculated but results from this thesis would suggest that copper concentrations in the region of 0.25 mM lead to 65% incorporation of copper. compared to 17% when no copper is added to the E. coli growth medium. E. coli cells were shown to grow with no apparent inhibition of growth in 3.0 mM of CuSO4. This concentration of copper in the growth medium may allow the production of a much higher ratio of copper-azurin compared to zinc-azurin than has been achieved so far.
Keywords: Azurin; Copper proteins; Organic electrochemistry; Alcaligenes; Analysis